Executive and management attitudes towards corporate social responsibility in Malaysia - Abdul Rashid, Md Zabid; Ibrahim, Saadiatul (Emerald, 2002)
Examines the attitudes of Malaysian managers and executives towards social responsibility and also the extent of socially responsible activities involved, corporate disclosure, and the factors determining the attitudes towards social responsibility. A structured questionnaire was developed based on studies by Ford and McLaughin, Teoh and Gregory Thong, Gill and Leinbach and Jones. A total of 198 responses were used for analysis in this study. The results showed that only five statements (of the 14 statements) have scores of more than 50 per cent agreement or endorsement of socially responsible activities. About 69 per cent of the respondents believed that involvement by a business in improving its community’s quality of life will also improve long run profitability. Nearly 65 per cent agreed that socially responsible activities provide a favourable public image. The analysis of variance showed that there were significant differences in the attitudes of managers working in banking, telecommunication, manufacturing and construction towards social responsibility. Nearly all of the respondents agreed that their companies were involved in socially responsible activities, that they were responsive to consumers’ complaints (83 per cent), and that they were maintaining product/service quality (77 per cent). Of the respondents nearly 54 per cent mentioned that their companies informed the general public of their socially responsible activities. The results also showed that the most influential factor determining the attitude towards social responsibility was family upbringing. The other important factors were traditional beliefs and customs, and common practices in the industry. Discusses the implications of the findings.